Attribution of runoff changes in the Danjiang River Basin in the Qinba Mountains, China - Zhao, Lei; He, Yi; Liu, Wanqing (Frontiers in Forests and Global Change, 2023)
The Danjiang River Basin has experienced significant alterations to its runoff patterns in recent years, primarily as a result of climate change and anthropogenic activities. This study aims to investigate these factors' influence on the basin's runoff between 1960 and 2016 using the Mann-Kendall (M-K) test and Accumulative Anomaly Curve (AAC) to assess the abrupt change characteristics of runoff. Furthermore, the study evaluates the effects of climate and anthropogenic factors on runoff evolution using eight independent Budyko hypotheses. The findings indicate that annual precipitation in the basin remained stable (P > 0.1), while annual runoff decreases significantly to -4.08mm/a (P < 0.05) and the annual potential evapotranspiration slightly decreases to -1.76mm/a (P < 0.05). The study also reveales that the reduction of runoff is primarily attributable to anthropogenic activities, contributing between 133.66% and 147.50%, while climate change contributes between -33.66% and -47.50%. The increased vegetation cover in the basin is identified as the primary cause of the reduction in runoff production and increase in evapotranspiration. Additionally, the construction of hydraulic engineering facilities in the basin is found to have had some impact on reducing runoff. These findings have significant implications for water resource management and soil and water conservation in the Danjiang River Basin.